Pengaruh Perasan Daun Kamboja (Plumeria acuminata) Terhadap Kematian Lalat Rumah (Musca domestica) - Rosida; Dewi Puji Lestari; Amaliyah Nurul Hidayah; Hadi Barru H.F.S (STIGMA: Jurnal Matematika dan Ilmu Pengetahuan Alam Unipa, 2022)
Flies are insects that act as vectors of mechanical disease, because disease agents such as pathogenic bacteria do not change in the fly's body but only move disease agents from polluted places to clean places. Flies can be controlled with plant-based insecticides. The purpose of this study was to determine the effect of frangipani leaf juice (Plumeria acuminata) on the death of house fly (Musca domestica). This research is an experimental research with the design of "Post Test Only With Control Group Design". The concentration of juice used is 70%, 80%, 90%, 100%. Each treatment was tested on 10 flies with three replications. Each concentration was tested by spraying on the flies with three sprays and observations were made every 10 minutes for one hour. The results of the study were analyzed using linear regression with a 95% confidence level. The results showed that there was an effect of frangipani leaf juice on the death of house flies (p = 0.00). Based on the results, it can be concluded that the juice of frangipani leaves (Plumeria acuminata) has an effect on the death of the house fly (Musca domestica). Keywords: kamboja leaves, house filies, vegetable insecticide